The Emotional Landscape of ‘Inside Out’: a Critical Analysis - Sahril Mujani; Thalia Ruliandara; Revida Engelbertha (STIBA IEC JAKARTA, 2024)
This research topic is the interpretation of signs of emotions in the main character’s behavior. More specifically, this study aims to recognize and represent the emotions depicted in Inside Out. ‘Inside Out’ displayed five emotions: Joy, Sadness, Anger, Fear and Disgust. Emotions in inside-out movies are interpreted by the signs implied in them. The approach used in this research is qualitative research. The qualitative method with descriptive analysis uses non-numerical data to comprehensively and accurately describe a specific event, behavior, or experience. This study uses several approaches and theories. Approaches used semiotics with Peircean theory and psychology with Schachter-Singer’s Two-Factor Theory of Emotion and cognitive arousal theory. The data were collected from scenes, scripts, and the movie’s dialogue. This research shows different meanings for signs, objects, and interpretants—the representation of basic emotions in the film ‘Inside Out.’ The result is dominant signs in cutting scenes with specified physical characteristics and clothing criteria. Therefore, emotions can arise because of physical reactions and cognitive interpretation of external stimuli. Cognitive processing interacts to drive a person’s behavior.